Pengaruh Persepsi Harga dan Kualitas Produk terhadap Keputusan Pembelian : pada Konsumen Kue Erna Cake Pancatengah Kabupaten Tasikmalaya - Doni Setiawan; Kusuma Agdhi Rahwana; Suci Putri Lestari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of price perception and product quality on purchasing decisions (a survey of consumers of Erna Cake Pancatengah, Tasikmalaya Regency). The method used in this study is causality through a survey approach. With a research sample of 100 consumers of Erna Cake Pancatengah, Tasikmalaya Regency. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that the perception of price and product quality had a significant influence on purchasing decisions on Erna Cake Pancatengah, Tasikmalaya Regency. Partially, price perception has a significant influence on purchasing decisions on Erna Cake Pancatengah, Tasikmalaya Regency. Partially, product quality has a significant influence on purchasing decisions on Erna Cake Pancatengah, Tasikmalaya Regency